Growth and yield responses of BARI Gom-26 (Triticum aestivum L.) to naphthalene acetic acid (Dhaka University Journal of Biological Sciences, 2013)
The effect of various concentrations of NAA (0, 25, 50, 75, 100 mg/l) on the growth and yield components of BARI Gom-26 was investigated. Data recorded on plant height, number of tillers per plant and number of leaves per plant showed negative performance in most cases with a few exceptions (7 and 14 DAS due to 25 and 50 mg/l NAA). The 50 mg/l NAA produced the highest total dry matter (TDM) at all the stages of growth except at 21 and 28 DAS and significant variations were observed at 7 DAS. Length of spike, grains per spike and 1000- seed weight increased following all the rates of NAA applications. Number of effective tillers and maximum yield (g/plant and t/ha) increased significantly only due to application of 50 mg/l NAA and the increases were 9.09 and 12.24% higher over the control, respectively. Non-effective tillers per plant decreased with all concentrations of NAA application and the maximum decrease (60.20%) was recorded with 50 mg/l NAA. Non-significant highest harvest index was also recorded with 50 mg/l followed by 100 mg/l NAA application.Dhaka Univ. J. Biol. Sci. 22(2): 119-125, 2013 (July)